Development of Corporate Social Responsibility (CSR) in India - Shankar, Ravi; Chadwick, Leslie; Ghafoor, Shahzad; Khan, Uzair Farooq (Journal of Asian Scientific Research, 2011)
The interest in Corporate Social Responsibility (CSR), which recognizes that companies have obligations that extend beyond short-run profit maximization to include notions of social and environmental concern, has increased considerably in recent decades. The globalization of the world economy and the related trade liberalization has brought forward a discussion of the importance of business as an actor in the development of society. The aim of this research is to analyse the effectiveness of the CSR strategies of international companies in terms of their impact on development in the host country. This will be performed as a case study of CSR in India. India constitutes a location with significant potential for international companies to contribute to development through CSR since it is an open nation with substantial international presence but still faces challenges regarding poverty alleviation and inequalities. Very little academic literature examines the development effects of CSR. In order to undertake this analysis, an analytical tool will be established that will present key characteristics of efficient CSR in terms of its impact on development. These key characteristics will be derived from the theory of new institutional economics, and will primarily argue that in order for CSR strategies to achieve the greatest efficiency, they must adhere to the institutional framework of the host context. The case study of the research will outline the nature of the international companies’ CSR strategies in India and evaluate them according to this analytical framework. The findings of the research indicate that the development effects of the contemporary CSR strategies in India are modest. However, CSR is a relatively recent amendment to the corporate agenda and it has potential to increase in efficiency and importance in the future.